Perbandingan Whey Keju Dan Susu Segar Terhadap Karakteristik Stirred Yoghurt Probiotik Dengan Lacticaseibacillus paracasei RB210 - Putri Suci Maharani; Ni Nyoman Puspawati; Sayi Hatiningsih (Study Program of Food Technology, Faculty of Agricultural Technology, Udayana University, 2026)
The utilization of cheese whey as a raw material for stirred yoghurt production has potential as an alternative waste management solution. Whey has weak protein aggregation properties, thus it needs to be combined with fresh milk, which contains casein with stronger hydrophobic interactions, to improve yoghurt structure. This study aimed to evaluate the effect of cheese whey and fresh milk ratios on the characteristics of probiotic stirred yoghurt and to determine the optimal ratio using Lacticaseibacillus paracasei RB210. Completely Randomized Design (CRD) was used with five treatments cheese whey to fresh milk ratios of 80:20, 70:30, 60:40, 50:50, and 40:60. Each treatment was repeated three times (15 experimental units). Observed variables included total lactic acid bacteria (LAB), total acidity, pH, fat content, viscosity, and sensory attributes (color, aroma, texture, taste, and overall acceptance). Data were analyzed using Analysis of Variance (ANOVA), followed by Duncan's Multiple Range Test (DMRT) when significant effects were found. The results showed that the whey-to-milk ratio significantly affected total acidity, pH, fat content, viscosity, and sensory properties, but not total LAB. The best treatment was the 60:40 ratio, producing yoghurt with 9.32 log CFU/ml LAB, 0.51% acidity, pH 4.55, 0.15% fat, viscosity of 1.23 P.as, and favorable sensory characteristics yellowish-white color, sour taste, slightly thick texture, and good overall acceptance.